ANALISIS MIKROSTRUKTUR LAPISAN TIPIS TiO2:ZnO YANG DIDEPOSISIKAN DIATAS SUBTRAT KACA DENGAN METODE SPRAY COATING UNTUK DEGRADASI LIMBAH ZAT WARNA - Wilda Amananti (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2017)
TiO2 is known as a good material candidate for environmental pollutant degradation. A combination of ZnO and TiO2 in the hope of enhancing the ability of ZnO in degrading the dye liquids. Precursor solutions TiO2, ZnO and TiO2: ZnO are deposited using sol-gel method of Spray Coating Technique. Microstructures of TiO2 and TiO2: ZnO thin films with and without the ZnO buffer layer were observed using X-Ray Diffraction (XRD). The photocatalyst activity was tested on Direct Blue degradation. The results conclude that TiO2: ZnO and ZnO thin films can form well above the glass substrate shown by the appearance of peaks of either ZnO or TiO2. But for TiO2 thin layers do not munujukan good results. The incorporation of TiO2: ZnO causes a lattice strain on the thin TiO2: ZnO film resulting in the narrowing of the energy band gap, resulting in increased photocatalytic capability of the thin film. TiO2: ZnO thin film has better photocatalytic capability than TiO2 or ZnO thin films.